Reversion of a methicillin resistant staphylococcus aureus strain to sensitivity in vivo : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University - De Malmanche, Sheree Alice (Massey University, 1993)
In 1986 during an outbreak of MRSA infection at Palmerston North Hospital an MRSA strain (PN MRSA) was recovered from a patient who was treated and subsequently discharged. In 1990 prior to readmission an isolate of S.aureus which produced small colonies typical of MRSA was recovered from the same patient. This isolate was resistant to several antibiotics but unexpectedly was sensitive to methicillin. This investigation examines the possibility that this atypical methicillin sensitive S.aureus (AMSSA) strain was derived in vivo from the resistant strain, possibly by a reversible mutation, and examines the possibility that exposure of this sensitive strain to analogues of methicillin may lead to reversion to resistance. The PN MRSA and the AMSSA strain were compared with various other methicillin resistant and sensitive staphylococci by phage typing, reverse phage typing, plasmid profiles, and total genomic digests using the restriction enzymes Hindlll and Smal. In all instances results showed that the PN MRSA and the AMSSA strain were more similar to each other than they were to any of the other staphylococci examined. Probing of total genomic and SmaI-digested DNA with the methicillin resistance gene mec showed that the gene was present in all the 'high level multiply resistant' and 'low level singularly resistant' MRSA strains examined but absent from the AMSSA strain and the other methicillin sensitive isolates. The 143 kb fragment which contained the mec gene in the PN MRSA was absent from the SmaI restriction profile of the AMSSA strain. The loss of this fragment and another fragment (104 kb) followed by the gain of a 203 kb fragment in the profile of the AMSSA strain was consistant with a deletion (44 kilobases) which spans a SmaI site. The deletion corresponds to the estimated size of the mec gene complex. Overall the results suggest that the AMSSA strain was derived in vivo from the PN MRSA strain and in the process 44 kilobases of DNA was deleted from the mec region. As sensitivity in the AMSSA strain was not due to an easily reversible point mutation or small deletion it is unlikely that the isolate will rapidly develop resistance to methicillin following exposure to the drug. However the results suggest that the mec region is unstable and that under the appropriate conditions the mec region may be lost from the chromosome of MRSA strain in vivo.
Keywords: Staphylococcal infections; Prevention; Staphylococcus aureus